2020
DOI: 10.1002/gepi.22288
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome‐wide association study of breast cancer risk by estrogen‐receptor status

Abstract: Previous transcriptome‐wide association studies (TWAS) have identified breast cancer risk genes by integrating data from expression quantitative loci and genome‐wide association studies (GWAS), but analyses of breast cancer subtype‐specific associations have been limited. In this study, we conducted a TWAS using gene expression data from GTEx and summary statistics from the hitherto largest GWAS meta‐analysis conducted for breast cancer overall, and by estrogen receptor subtypes (ER+ and ER−). We further compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 54 publications
(83 reference statements)
1
29
0
1
Order By: Relevance
“…Through eQTL analysis with the GTEx database and further gene expression assay on CRISPR/Cas9 genome-edited cells, we identified ATP6AP1L to be the target gene for rs10514231. TWAS (transcriptome-wide association study) analysis identified that the ATP6AP1L gene was significantly associated with breast cancer risk [35]. It was also reported that the increased expression of ATP6AP1L was associated with decreased breast risk [36].…”
Section: Discussionmentioning
confidence: 98%
“…Through eQTL analysis with the GTEx database and further gene expression assay on CRISPR/Cas9 genome-edited cells, we identified ATP6AP1L to be the target gene for rs10514231. TWAS (transcriptome-wide association study) analysis identified that the ATP6AP1L gene was significantly associated with breast cancer risk [35]. It was also reported that the increased expression of ATP6AP1L was associated with decreased breast risk [36].…”
Section: Discussionmentioning
confidence: 98%
“…Independently significant TWAS risk genes by TIGAR Out of these 88 significant TWAS genes for breast cancer by TIGAR, 20 genes are known GWAS risk genes of breast cancer 11,[41][42][43][44][45][46][47][48] , 64 are located within 1MB region of a previously identified GWAS loci of breast cancer 11,[41][42][43][44][45][46][47][48] (Table S2), and 35 genes are identified by previous TWAS 21,39,[49][50][51][52] . Similarly, out of these 37 significant TWAS genes for ovarian cancer by TIGAR, 34 genes are located on chromosome 17 including two known GWAS risk genes (NSF and PLEKHM1) 12,53,54 , 33 genes are located within 1MB of these two known GWAS risk genes (Table S3), and 13 genes (including NSF 55 ) are identified by previous TWAS 39,55,56 .…”
Section: Twas Of Breast and Ovarian Cancermentioning
confidence: 99%
“…The development of TWAS and important considerations in their application and interpretation have been reviewed in detail elsewhere (Wainberg et al, 2019; Zhu & Zhou, 2020). TWAS have successfully identified novel risk loci and candidate susceptibility genes for many complex human traits, including cancers, schizophrenia, type 2 diabetes, smoking behavior, body mass index, and four traits related to the well‐being spectrum (Baselmans et al, 2019), among others (Feng et al, 2020; Gusev et al, 2018; Mancuso et al, 2018; TWAS HUB; Wu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%